The diversification of thecae horns and their putative significance—a case study of Schismatoglottideae (Araceae) - Shook Ling, Low; Sin Yeng, Wong (Springer, 2022)
Thecae horns are specialized anther extensions present in two tribes of Araceae: Cryptocoryneae and Schismatoglottideae. This structure is important in defning the generic boundaries and segregations within Schismatoglottideae. Eleven convergent lineages of thecae horns have evolved within Schismatoglottideae, contributing to the diverse stamen structures and thecae orientations. Here, we investigated the stamens of 22 taxa belonging to eight genera (Aridarum, Burttianthus, Hera, Heteroaridarum, Pursegloveia, Naiadia, Tawaia, and Toga) of Schismatoglottideae. We assessed the foral biology by focusing on the angle and movement of the thecae horns during the pistillate and staminate phases of anthesis. The angle of the thecae horns changed at the start of anthesis and, in several species, elevated further during staminate anthesis. Papillae cells, smooth or verrugated surface, are present on the thecae horns with the excavated connective often found to be smooth vs. non excavated connective, with verrugated surface. The presence of calcium oxalate packages decreases from pistillate phase to staminate phase of anthesis and is postulated to be a defense mechanism against predators.